2008
DOI: 10.1002/hep.22382
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphism analysis of the multidrug resistance protein 3 gene for the detection of clinical progression in Japanese patients with primary biliary cirrhosis

Abstract: Primary biliary cirrhosis (PBC) is a multifactorial disease in which genetic factors rather than environmental factors may predominantly contribute to the pathogenesis. In order to identify the genetic determinants of the disease severity and progression of PBC, we examined an association of seven tag single-nucleotide polymorphisms (SNPs) in the multidrug resistance protein 3 (MDR3/ABCB4) gene in 148 Japanese PBC patients and 150 age-and sex-matched healthy control subjects. SNPs were detected via polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In other words, GGT and IgM levels appear to represent PBC disease activity. Our results support recent reports using singlenucleotide polymorphism analysis, which showed that MDR3 haplotypes and diplotypes are associated with the progression of PBC [21,22]. In this study, the patients, in whom GGT and IgM levels were already elevated (Table 2), were in the early stages and without any medication for PBC.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, GGT and IgM levels appear to represent PBC disease activity. Our results support recent reports using singlenucleotide polymorphism analysis, which showed that MDR3 haplotypes and diplotypes are associated with the progression of PBC [21,22]. In this study, the patients, in whom GGT and IgM levels were already elevated (Table 2), were in the early stages and without any medication for PBC.…”
Section: Discussionsupporting
confidence: 92%
“…CTLA4 and SLC4A2 SNPs were analyzed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and TaqMan SNP Genotyping assays as previously described [6,10]. All primers and probes for the TaqMan SNP Genotyping assays were purchased from Applied Biosystems (Foster City, CA, USA).…”
Section: Dna Preparation and Genotypingmentioning
confidence: 99%
“…Many candidate gene association studies have been performed and several single nucleotide polymorphisms (SNPs) have been associated with PBC, including human leukocyte antigen (HLA), cytotoxic T-lymphocyte antigen 4 (CTLA4), solute carrier family 4 anion exchanger, member 2 (SLC4A2), tumor necrosis factor, and programmed cell death 1 and multidrug resistance protein 3 [2][3][4][5][6][7][8][9][10][11][12][13]. In addition to these genes, recent genome-wide association studies have revealed that IL12A, IL12RB2, IRF5-TNPO3, 17q12-21, and MMEL1 loci were associated with PBC susceptibility in Caucasians [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Among the non-HLA loci, strong association signals with PBC were found for SNPs in IL12A, IL12RB, STAT4, CTLA4, DEN-ND1B, CD80, IL7R, CXCR5, TNFRSF1A, CLEC16A and NFKB1 [11]. Furthermore, HLA [37] and non-HLA gene polymorphisms (MDR3, A2BP1) [38,39] have also been implicated with the onset or progression of PBC. Endothelin polymorphisms have been investigated in cardiovascular diseases and hypertension, but there are also a few reports in other autoimmune diseases such as vitiligo [40], psoriasis [41], scleroderma [42], primary Raynaud [43].…”
Section: Discussionmentioning
confidence: 99%